Giving the Past a Future: Community Archaeology, Youth Engagement and Heritage in Quinhagak, Alaska - Hillerdal, Charlotta; Watterson, Alice; Williams, M. Akiqaralria; Alaskuk Strunk, Lonny; Nalikutaar Cleveland, Jacqueline; Joseph, Corey Al’aq (Études Inuit Studies, 2022)
Initiated by the descendant community of Quinhagak and endorsed by village Elders, the Nunalleq Archaeology Project was unique for Yup’ik Alaska when it began in 2009. Since then, this embedded community project has provided the village with over a decade of archaeological presence in the form of excavations, finds processing, conservation lab work, and, since 2018, a local repository housing the entire archaeological collection.Accounts of collaborations between archaeologists and Indigenous communities often focus on Elders and cultural bearers. However, whilst these collaborators are, and continue to be, invaluable for the Nunalleq project, here we want to acknowledge the generation of young adults who have grown up with the Project, and to whom archaeological finds and artifacts are now an intrinsic part of their heritage. This paper discusses how the Nunalleq Archaeology Project has come to influence local heritage, and how community engagement has in turn shaped the archaeological practice and co-designed outreach work. We constructively reflect upon insights borne from a decade of collaborative practice and critically ask how such community collaborations may be strengthened for the future. Initié par la communauté des descendants de Quinhagak et approuvé par les Aînés du village, le Projet Archéologique de Nunalleq était unique pour l’Alaska Yup’ik lorsqu’il a débuté en 2009. Depuis lors, ce projet communautaire intégré a fourni au village plus d’une décennie de présence archéologique sous la forme de fouilles, du traitement des découvertes, de travaux de conservation en laboratoire et, depuis 2018, un dépôt local abritant l’ensemble de la collection archéologique.Les récits de collaborations entre archéologues et communautés autochtones se concentrent souvent sur les Aînés et les détenteurs culturels. Cependant, bien que ces collaborateurs soient et continuent d’être inestimables pour le projet Nunalleq, nous tenons ici à remercier la génération de jeunes adultes qui ont grandi avec le projet et pour ...